PERFORMANCE OF PACIFIC WHITE SHRIMP FED PROBIOTICS Lactobacillus plantarum AND Bacillus spp. IN A BIOFLOC SYSTEM - Norha Constanza BOLÍVAR-RAMÍREZ; Ana Clara Chede Pereira SILVA; Gabriela Soltes FERREIRA; Walter Quadros SEIFFERT; Felipe do Nascimento VIEIRA (Boletim do Instituto de Pesca)
The present study evaluated the use of the indigenous probiotic Lactobacillus plantarum and commercial probiotic containing Bacillus spp. in the culture of L. vannamei in a biofloc system. Shrimp  were fed with four diets: L. plantarum, Bacillus spp., L. plantarum + Bacillus spp. and feed with no additives. Growth performance, water quality variables and microbiological counting of water and digestive tract of shrimp  were determined. The control group and L. plantarum treatment showed better growth performance. The highest feed conversion ratio (FCR) and the lowest survival were obtained in the L. plantarum + Bacillus spp. treatment, which had significantly higher nitrite values. Vibrio spp. counts in the water were lower in the L. plantarum and L. plantarum + Bacillus spp. treatments and were lower in the intestinal tract in the L. plantarum treatment. Lactic acid bacteria (LAB) was higher in the L. plantarum treatment in the water and digestive tract. The count of total heterotrophic bacteria (THB) deferred only among Bacillus spp. and L. plantarum + Bacillus spp. treatment, being higher in the latter group. In Bacillus spp. treatment, no presence of LAB was detected in the water or intestinal tract. We conclude that the use of L. plantarum combined with Bacillus spp. negatively affected survival, FCR and water quality, but that the use of L. plantarum alone reduced the presence of Vibrio spp., even though it did not change the growth performance of L. vannamei.